Rethinking Space: Planning Theories for Sustainable Tourism in Gunung Kidul, Indonesia - Fikri, Muhammad Adymas Hikal; Rajib, Rayi Kharisma; Hidayah, Nur; Aprilia, lsabila Nisa; Insanidya, Safira Embun; Prasetyo, Andi Yudha (Indonesian Journal of Agrarian Law, 2024)
Gunungkidul Regency is one of the regions that has experienced significant growth in the tourism sector in the last two decades. The beauty of the karst landscape, underground caves, and the series of southern beaches are major attractions for both domestic and international tourists. Amidst this development, challenges arise in managing space that balances economic interests and environmental preservation. The use of space for tourism purposes is often inconsistent with established spatial plans, resulting in conflicts over spatial use, damage to karst ecosystems, and shifts in the function of protected areas. This study aims to critically examine theories and approaches to spatial planning and evaluate the extent to which these approaches are applied in sustainable tourism development in Gunungkidul Regency. The approach used is a juridical-sociological one, examining the relationship between spatial planning legal norms and empirical conditions in the community. Data collection techniques were carried out through interviews with policymakers and tourism actors, direct observation of tourism development locations, and literature studies of planning documents such as the RTRW (Regional Spatial Plan), RDTR (Regional Spatial Plan), and regional regulations. The results show that the spatial planning approach that has been applied to date tends to be top-down and technocratic, thus lacking the involvement of local communities as the primary subjects of development. Mismatches between planning and implementation persist, particularly in the form of zoning violations and weak oversight of land use conversion.